2019
DOI: 10.1155/2019/1935806
|View full text |Cite
|
Sign up to set email alerts
|

Osteoarthritis, Exercise, and Tissue Engineering: A Stimulating Triad for Health Professionals

Abstract: Osteoarthritis (OA) is a degenerative disease, promoted by abnormal chronic mechanical loading over the joint, for instance, due to excessive body mass. Patients frequently report pain, fatigue, and limitations in specific functional daily activities. Regarding the treatment of OA, two nonpharmacological options are available. However, it is not clear which type and intensity of exercise have better outcomes in treatment and how tissue engineering can be a promising field due to the mechanical load implants wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…The goal of CTE is to modify the host microenvironment of OA and promote cartilage regeneration ( Ondresik et al, 2017 ). Successful tissue engineering depends on multiple aspects, including appropriate cells for implantation, well-designed scaffolds for mechanical support, and biological factors for directing cells to differentiate in the proper direction ( Liu Y. et al, 2017 ; Morouco et al, 2019 ). Recent investigations have highlighted its promising, and some strategies are already available on the market ( Brittberg, 2008 ; Evans et al, 2018 ).…”
Section: Non-surgical Application Of Cartilage Tissue Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…The goal of CTE is to modify the host microenvironment of OA and promote cartilage regeneration ( Ondresik et al, 2017 ). Successful tissue engineering depends on multiple aspects, including appropriate cells for implantation, well-designed scaffolds for mechanical support, and biological factors for directing cells to differentiate in the proper direction ( Liu Y. et al, 2017 ; Morouco et al, 2019 ). Recent investigations have highlighted its promising, and some strategies are already available on the market ( Brittberg, 2008 ; Evans et al, 2018 ).…”
Section: Non-surgical Application Of Cartilage Tissue Engineeringmentioning
confidence: 99%
“…Tissue engineering is thought a reparative treatment that mainly targets interference at the early stages of OA to maintain and restore the extracellular matrix (ECM) of cartilage ( Liu Y. et al, 2017 ). It offers a possibility to regenerate cartilage by using cells, scaffolds, and genes alone or combined ( Morouco et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the exploration and investigation of reparative and regenerative alternatives that will result in more physiological and long-lasting results are needed. In this regard, tissue engineering has become an attractive alternative [ 5 , 6 ] since it involves the combined use of different cell types, scaffolds, growth factors, and physical stimulation to regenerate living tissue [ 7 ]. Among the most used cells are the mesenchymal stem cells (MSCs), responsible for the maintenance of adult tissues [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Available at www.veterinaryworld.org/Vol.15/July-2022/35.pdf Tissue engineering has gained increasing interest and developed to apply for cartilage restoration in humans and animals [3,4]. Several studies have reported appropriate cell sources, biocompatible and biodegradable scaffolds, effective growth factors, and suitable techniques to generate cartilage tissue ex vivo for in vivo implantation [5][6][7].…”
Section: Introductionmentioning
confidence: 99%